Fostering Students’ Statistical Literacy Through Significant Learning Experience - Krishnan, Saras (Hipatia Press, 2015)
A major objective of statistics education is to develop students’ statistical literacy that enables them to be educated users of data in context. Teaching statistics in today’s educational settings is not an easy feat because teachers have a huge task in keeping up with the demands of the new generation of learners. The present day students have higher expectations in terms of classroom pedagogy particularly in the use of creative and engaging methods to create a significant learning experience for them. This paper discusses how students’ statistical literacy can be fostered by creating a more integrated statistics course using the Fink’s Taxonomy of Significant Learning.